Impact of Ball-Milling Pretreatment on Pyrolysis Behavior and Kinetics of Crystalline Cellulose - Khan, A.S. (Springer Netherlands, 2016)
Effect of ball-milling pretreatment on pyrolysis characteristics of cellulose was studied by thermogravimetric analysis (TGA) at four different heating rates; 5, 10, 20, and 40Â K/min. Variation in the thermal stability and activation energy of cellulose with ball-milling were calculated by TGA Kinetics using Kissinger, KissingerâAkahiraâSunose, FlynnâWallâOzawa and Starink model free methods. Results demonstrated that ball-milling reduced the thermal stability and activation energy of cellulose. The original and ball-milled cellulose were thoroughly characterized by Fourier-transform infrared spectroscopy, X-ray diffraction, and Scanning electron microscopy. X-ray diffraction analysis revealed that ball-milling decreased the crystallinity of cellulose from 93 to 51Â . The results suggested that ball-milling pretreatment led to effective disruption of crystalline cellulose to amorphous cellulose. It is, therefore, concluded that the ball-milled cellulose can easily become a useful source of chemicals and energy than crystalline cellulose. Â© 2015, Springer Science+Business Media Dordrecht.